Screening for chemicals that affect hair cell death and survival in the zebrafish lateral line - Ou, Henry (2012)
The zebrafish lateral line is an efficient model system for the evaluation of chemicals that protect and damage hair cells. Located on the surface of the body, lateral line hair cells are accessible for manipulation and visualization. The zebrafish lateral line system allows rapid screens of large chemical libraries, as well as subsequent thorough evaluation of interesting compounds. In this review, we focus on the results of our previous screens and the evolving methodology of our screens for chemicals that protect hair cells, and chemicals that damage hair cells using the zebrafish lateral line.